PROJECT-BASED STEAM MODEL LEARNING TO IMPROVE CREATIVE THINKING IN EARLY CHILDHOOD - Hasanah, Uswatun; Pradana, Pascalian Hadi (Universitas Al-Hikmah Indonesia, 2024)
The independent curriculum applied to early childhood today puts pressure on the development of creativity and gives freedom in learning. Finding a project-based STEAM approach that can improve early childhood creative thinking is the goal of this study. This research was conducted to apply varied learning to develop children's creative thinking with the appropriate learning model and in accordance with the current school needs. The research techniques applied in PTK, or class action research. Methods of gathering data that combine documentation as well as observation. Diagrams are then used to apply the observations' findings to see the progress of each cycle. From the exposure of each cycle can be seen at the time of pre-cycle there are still students who get low scores, then develop in the cycle one pupils who get very good scores and continue to increase in the second cycle where most pupils get excellent scores. The findings in this study to know how project-based STEAM learning can enhance creative thinking in early childhood are shown when learning begins to vary and students can create their own results without the help of others and can produce different forms or works according to the creative ideas of each student. According to the study's findings, fifteen pupils obtained great scores., 3 students received grades that matched expectations. With a project-based STEAM model, we can prepare future generations for the increasingly complex challenges of the world by expanding STEAM models for early childhood.